Synthesis of Core-Shell @@ Microspheres and Their Application as Recyclable Photocatalysts - Zhenghua Wang; Ling Shen; Shiyu Zhu (International Journal of Photoenergy)
We report the fabrication of core-shell Fe3O4@SiO2@TiO2 microspheres through a wet-chemical approach. The Fe3O4@SiO2@TiO2 microspheres possess both ferromagnetic and photocatalytic properties. The TiO2 nanoparticles on the surfaces of microspheres can degrade organic dyes under the illumination of UV light. Furthermore, the microspheres are easily separated from the solution after the photocatalytic process due to the ferromagnetic Fe3O4 core. The photocatalysts can be recycled for further use with slightly lower photocatalytic efficiency.